Association Between Hypertensive Disorders During Pregnancy and Subsequent Long-term Risk of Hospitalization Due to End-stage Renal Disease: A Population-based Follow-up Study - Dai, Li (Université d'Ottawa / University of Ottawa, 2015)
Hypertensive disorders during pregnancy (HDPs) were reported to be associated with some serious maternal outcomes and adverse long-term consequences. To examine the effect of HDPs on the development of end-stage renal disease (ESRD), we followed up a cohort of women who had delivered in Canadian hospitals between the fiscal years of 1993/1994 and 2002/2003 and identified their subsequent hospitalizations. The study revealed that a significantly higher risk of incidence of subsequent ESRD hospitalization was associated with previous HDPs, and women with pre-eclampsia superimposed on pre-existing hypertension had the highest risk among the women with HDPs. Cox regression analysis was used to adjust for potential confounders, and to estimate the relative risk for ESRD hospitalization associated with previous HDPs and found that gestational hypertension and pre-eclampsia increased the risk which was partially mediated by diabetes mellitus developed after HDPs. In addition, pre-eclamptic pregnancy associated with preterm delivery could substantially elevated risk of an ESRD hospitalization in later life.